William Stevens Fielding: A Nova Scotia Liberal in National Politics - Cahill, Barry (Journal of the Royal Nova Scotia Historical Society)

(untitled) (Royal Nova Scotia Historical Society, 2023)
Among the six most important Nova Scotia Liberals in national politics— W. S. Fielding, D. D. McKenzie, J. L. Ralston, J. L. Ilsley, Robert Winters, and Allan MacEachen—William Stevens Fielding (1848–1929) stands pre-eminent. Born the year party-political government was achieved, Fielding founded a Liberal Party dynasty that ruled Nova Scotia continuously for four decades and, at nineteen years, he was Canada’s longest-serving minister of finance. Having nearly become prime minister in 1908, when Sir Wilfrid Laurier was on the verge of resigning, and nearly became leader of the Liberal Party after Laurier’s death in 1919, Fielding is a major figure in post-Confederation Canadian history. This article is an overview of his career.